Decision Support System For Student Activity Unit Selection Using Certainty Factor Method - Hayati, Nova; Shofia, Alima; Syaputra, Aldo Eko; Manurung, Kiki Hariani (Internet of Things and Artificial Intelligence Journal, 2024)
In various fields, including the selection of Student Activity Units on campus, Decision Support Systems (DSS) have become an important tool to assist the decision-making process. SPK provides information and analysis that is structured and easy to understand, thereby helping decision-makers to choose SMEs that best suit their interests, talents, and goals. Choosing the right Student Activity Units for students can contribute to the development of their personal qualities and help develop a variety of social and professional skills. Using the Certainty Factor method in creating a Decision Support System to assist students in choosing Student Activity Units that are most relevant to their desired interests and talents. The Certainty Factor method is an artificial intelligence technique that can overcome uncertainty in data and provide a level of confidence in every decision. Based on trials carried out on several interest and talent characteristics using the Certainty Factor method, percentage results were obtained with a confidence level of 80.26%. Based on the test results, it can be concluded that the expert system created can make it easier to determine talent interests that match student desires.